2021
DOI: 10.14201/eks.23915
|View full text |Cite
|
Sign up to set email alerts
|

Students' Characteristics Influence Readiness to Use Mobile Technology in Higher Education

Abstract: The purpose of the current study was to explore students' characteristics that influence student's readiness to use mobile technology at An-Najah National University in Palestine. The researchers used a quantitative approach to achieve the purpose of the study. 214 students from different schools were participated in the study. A descriptive and one-way ANOVA to test the hypotheses were used in data analysis stage. The findings of the study revealed that the availability of technology is an important factor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…By reducing the reliance on permanent locations for work and study, this mobility enables formal and informal learning contexts [16], which changes how students learn [17]. In Palestine's case, several studies [5,18,19] have been conducted on m-learning, where these studies have included several aspects of students' learning [20][21][22][23], but not their attitudes towards this learning.…”
Section: Mobile Technologies In Learningmentioning
confidence: 99%
“…By reducing the reliance on permanent locations for work and study, this mobility enables formal and informal learning contexts [16], which changes how students learn [17]. In Palestine's case, several studies [5,18,19] have been conducted on m-learning, where these studies have included several aspects of students' learning [20][21][22][23], but not their attitudes towards this learning.…”
Section: Mobile Technologies In Learningmentioning
confidence: 99%
“…An attempt has been made in this paper to look at how mobile devices might be used pedagogically by presenting methods for formally integrating them into higher education, guided by two major frameworks for group collaboration, referred to as Authentic Learning and Action Learning by the authors. It has been discovered that mobile technology is an effective tool for improving communication and learning (Shaqour et al, 2021). To promote and enhance student retention, the authors suggested SMS-based mobile technologies.…”
Section: Surroundingsmentioning
confidence: 99%
“…The first paper, titled Students' Characteristics Influence Readiness to Use Mobile Technology in Higher Education (Shaqour et al, 2021), aims to explore learners' characteristics which impact their readiness to use mobile technology. The results showed that the existence of this technology and the students' capability are the most influential factors of these students' readiness to use such technology.…”
Section: Summary Of Contributionsmentioning
confidence: 99%